1986
DOI: 10.2105/ajph.76.6.698
|View full text |Cite
|
Sign up to set email alerts
|

Trends in tobacco use on television.

Abstract: A two-week composite sample of prime time television programming from fall 1984 was analyzed for portrayals of alcohol and tobacco. Earlier studies note that smoking acts have progressively declined, suggesting smoking is no longer as frequent on prime time television. The current study notes higher levels of smoking. This could be an indication that smoking is returning, and/or related to recent programming changes featuring more dramas on prime time television. (Am J Public Health 1986; 76:698-699.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Other investigations have documented the prevalence of televised tobacco depictions within popular television series, such as The Simpsons, 21,22 and across multiseries samples that are designed to represent popular television more broadly. [23][24][25][26][27] The most recent data on US youth are from an Office of National Drug Control Policy study 28 conducted in 1998. The study found tobacco depictions in 20% and tobacco-related dialogue in 23% of the sampled episodes, which were drawn from the 20 top-rated situation comedies or dramas popular among US youth aged 12 to 17 years.…”
Section: For Editorial Comment See Page 181mentioning
confidence: 99%
“…Other investigations have documented the prevalence of televised tobacco depictions within popular television series, such as The Simpsons, 21,22 and across multiseries samples that are designed to represent popular television more broadly. [23][24][25][26][27] The most recent data on US youth are from an Office of National Drug Control Policy study 28 conducted in 1998. The study found tobacco depictions in 20% and tobacco-related dialogue in 23% of the sampled episodes, which were drawn from the 20 top-rated situation comedies or dramas popular among US youth aged 12 to 17 years.…”
Section: For Editorial Comment See Page 181mentioning
confidence: 99%
“…Although portrayal of tobacco in fictional television programs is less frequent, there is evidence that it was increasing during the early 1990s [118] after a period of decline during the 1980s [123,124]. Tobacco portrayal also occurs in music lyrics and music videos.…”
Section: Literature Review: Empirical Studiesmentioning
confidence: 99%
“…Previous quantitative research (8,9,11,(13)(14)(15)(16)22) has mainly focussed on the number of times a substance is used in the course of an hour on TV, and not on the actual number of characters using substances. These studies have given the impression that characters using addictive substances on TV are ubiquitous and far exceed actual rates of substance use in the U.S. population, whereas our results suggest that, at least for prime-time, the converse is true.…”
Section: Discussionmentioning
confidence: 99%